Analysis structural about Core Competency in Information and Communication Technology for Academy Staff Thaksin University - โชติการ, สุวรรณ; Kongnoo, Kritsada; Suwanmanee, Punyada; Sae-tae , Rungthip (National Interest, 2021)
This study aimed to identify information and communication technology core competencies of the academic staff of Thaksin University and develop information and communication technology core competencies of supporting staff evaluation form. In the first stage, the study was conducted to identify information and communication technology core competencies of the academic staff of Thaksin University through related documents and in-depth interviews of nine experts. Next, the data were analyzed by the Data Triangulation method, and results were used to form a structure of information and communication technology core competencies. Then, a focus group discussion with six experts was conducted to revise drafted core competencies for information and communication technology academic staff and weigh the selected ones. After that questionnaires on core competencies structure were given to the sample subject of 211 officials and academic staff, using the simple random sampling technique, to insist the core competencies in information and communication technology. The study revealed the following findings. The structure of core competencies in information and communication technology of the supporting staff of Thaksin University consisted of knowledge, skills, and attitude. The percentage of weight proportion of core competencies in information and communication technology of the supporting staff of Thaksin University in descending were skills - sixty percent, knowledge - thirty percent, and attitude – ten percent. The structure of core competencies in information and communication technology was reliable because the construct validity and convergent validity were at the good level and its coefficient of forecasting (R2) of between 0.49 and 0.88 showed that the majority member of each component were reliable.